Is an intra-Islamic theological ecumenism possible?: A response to Sherman Jackson ; review essay - Khalil, Atif (American journal of Islamic social sciences, 2005)
Rezension von: Jackson, Sherman A.; Gazzali, Abu-Hamid Muhammad Ibn-Muhammad al-: On the boundaries of theological tolerance in Islam: Abu Hamid al Ghazali's "Faysal al tafriqa bayna al-islam wa al-zandaqa". - Oxford ... : Oxford University Press, 2002